2015
DOI: 10.1523/jneurosci.1780-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Local Brain Blood Flow Control by Astrocytes Independent of Phasic Neurovascular Coupling

Abstract: According to the current model of neurovascular coupling, blood flow is controlled regionally through phasic changes in the activity of neurons and astrocytes that signal to alter arteriole diameter. Absent in this model, however, is how brain blood flow is tonically regulated independent of regional changes in activity. This is important because a large fraction of brain blood flow is required to maintain basal metabolic needs. Using two-photon fluorescence imaging combined with patch-clamp in acute rat brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 54 publications
2
92
0
1
Order By: Relevance
“…Cerebral COX-1 is expressed primarily in neurons, glia and endothelial cells [35][36][37] and has been suggested to play a role in maintaining resting vascular tone. 30,38 Constitutive expression of cerebral COX-2, however, is limited to excitatory neurons where, unlike COX-1, it is thought to mediate neurovascular coupling. 31,32,39 The reliance on COX-1 metabolites for the transformation of the hyperemic response to oligemia following CSD suggests that despite their massive depolarization, excitatory cortical neurons which primarily express COX-2, 40,41 are unlikely to contribute.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebral COX-1 is expressed primarily in neurons, glia and endothelial cells [35][36][37] and has been suggested to play a role in maintaining resting vascular tone. 30,38 Constitutive expression of cerebral COX-2, however, is limited to excitatory neurons where, unlike COX-1, it is thought to mediate neurovascular coupling. 31,32,39 The reliance on COX-1 metabolites for the transformation of the hyperemic response to oligemia following CSD suggests that despite their massive depolarization, excitatory cortical neurons which primarily express COX-2, 40,41 are unlikely to contribute.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Such dilution could potentially explain why in our study epidural SC-560 treatment (at 500 mM) did not reduce resting CBF while previous studies noted decreased resting CBF and cerebral vasoconstriction following parenchymal superfusion of this inhibitor at concentrations !10 mM. 30,38,50 Because SC-560, as well naproxen, affected CBF only during the oligemic stage, it is also tempting to speculate that these COX inhibitors are more efficient in blocking the synthesis of vasoconstricting prostanoids that mediate the post-CSD oligemia than inhibiting the formation of vasodilating prostanoids that control basal CBF. Nonetheless, given the uncertainty about the precise parenchymal concentration of the inhibitors in our study, the effects elicited by these agents should be interpreted with caution given the possibility that the inhibition was only partial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bimodal nature of neurovascular coupling In brain, it has been observed that there are two types of NVC that control changes in CBF [3]. One type is rapid [phasic] in response to increased glutamatergic neuron synaptic activity and characterized by release of nitric oxide (NO) generated by neuron nitric oxide synthase (nNOS) [4] and liberation of K + and free glutamate (Glu) to extracellular fluid (ECF).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rather than triggering a rapid vascular response, synaptic activity-evoked astrocyte calcium increases have been proposed to mediate sustained vascular responses to prolonged stimulation [40,43,44]. Furthermore, astrocytes also appear to play a role in maintaining the resting tone of the vasculature [45][46][47], which could affect the size of the blood flow response following neuronal activity [48].…”
Section: Cellular Mechanisms Underlying Bold: How Our Incomplete Undementioning
confidence: 99%